Student Overview of the Pancasila and Citizenship Education Study Program: Understanding Pancasila, Social Participation, and Perception as Agents of Change - Irianto, Petrus (PT FORMOSA CENDEKIA GLOBAL, 2024)
Higher education plays an important role in shaping student attitudes and personalities as drivers of social change. Although Pancasila is regarded as a moral and ethical guideline, students often face difficulties in applying these values in everyday life. The aim of this study is to evaluate students' understanding of Pancasila, their involvement in social change, and the way they see the challenge in the role of students as agents of change based on Pancasila. The study used a survey method with the population of Students of the Pancasila Education and Citizenship Studies Program at one of the Universities in Papua Province. Most respondents believe that Pancasila serves as a legal foundation and as a moral guideline; (2) the majority of respondents in this study are still engaged in social change movements or activities in the community and on campus, as well as showing strong commitment and awareness in building a better society; (3) raising public Awareness about Pancasil's policies is the main way respondents overcome difficulties in carrying out their duties as agents of change based on Pancasila. Educational institutions should care and support respondents in carrying out their duties as agents of change based on Pancasila.